Victims [compact disc, unabridged] : an Alex Delaware novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels, 2012)
By all accounts, acid-tongued Vita Berlin hadn't a friend in the world, but whom did she cross so badly as to end up arranged in such a grotesque tableau? One look at her apartment-turned-charnel house prompts hard-bitten LAPD detective Milo Sturgis to summon his go-to expert in hunting homicidal maniacs, Alex Delaware. But despite his finely honed skills, even Alex is stymied when more slayings occur in the same ghastly fashion.